Lexical variants as linguistic innovations in editions of F. Skoryna - Varonka, Krystsina P. (Journal of the Belarusian State University. Philology, 2019)
This article deals with the lexical variants, which define linguistic basis of F. Skoryna’s editions. The author analyzes algorithms of translation from original text and scheme of adaptation parts of word meaning according to the translation task. The aim of the article is a linguistic study of semantic transformations (adaptations) as a way to achievement lexical adequacy, functioning in translation. In article was defined meaning of the concepts variant, variation, double, scientific novelty of the article is to identify the linguistic variants in their classification.
Keywords: variant; variation; synonym; translation strategy; lexis